2020
DOI: 10.1111/1750-3841.15168
|View full text |Cite
|
Sign up to set email alerts
|

Effects of superfine grinding on asparagus pomace. Part I: Changes on physicochemical and functional properties

Abstract: The effects of superfine grinding on the physicochemical and functional properties of asparagus pomace were investigated. The results showed that in terms of the specific surface area, water solubility, soluble dietary fiber content, and ratio of insoluble dietary fiber to soluble dietary fiber, finer samples usually possessed better physicochemical properties compared with coarse samples. However, grinding samples excessively to produce small particle sizes could reduce the water‐holding capacity, oil‐binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…A significant PS reduction was observed with increasing milling time from 5 to 10 h. Under the same conditions (BM time: 10 h), taro peel presented the largest average granule diameter (31.20 μm), followed by yam (20.28 μm) and sweet potato (13.91 μm). The reduction in PS and increase in specific SA have also been observed in BM-treated mulberry leaves (Chen et al 2015), onion peel (Jiang et al, 2020), asparagus pomace (Gao et al, 2020) and white winter bran (He et al, 2018). M. described the changes in viscosity as a result of structural modifications.…”
Section: Effect On Physicochemical and Functional Properties Of Dieta...mentioning
confidence: 77%
See 2 more Smart Citations
“…A significant PS reduction was observed with increasing milling time from 5 to 10 h. Under the same conditions (BM time: 10 h), taro peel presented the largest average granule diameter (31.20 μm), followed by yam (20.28 μm) and sweet potato (13.91 μm). The reduction in PS and increase in specific SA have also been observed in BM-treated mulberry leaves (Chen et al 2015), onion peel (Jiang et al, 2020), asparagus pomace (Gao et al, 2020) and white winter bran (He et al, 2018). M. described the changes in viscosity as a result of structural modifications.…”
Section: Effect On Physicochemical and Functional Properties Of Dieta...mentioning
confidence: 77%
“…The fiber composition and process conditions had a profound impact on the extent of PS reduction. Recently, Gao et al (2020) reported a significant reduction in PS from 109.3 to 24.4 μm in asparagus pomace subjected to BM (12000 rpm/3 h). Huang et al (2010) evaluated the impact of processing time on the PS of peels of three root and tuber crops as sources of DF.…”
Section: Effect On Physicochemical and Functional Properties Of Dieta...mentioning
confidence: 99%
See 1 more Smart Citation
“…Water absorption index is important in foods where water will be imbibed without the dissolution of protein, thus increasing their viscosity and body thickening (Amin et al, 2021). A direct relationship was reported to exist between increasing fibre size and the volume of trapped water (Gao et al, 2020). The decrease in the water absorption index of samples can be attributed to milling operation and thermal treatments given to coconut residue during preparation damaged the fibre chains and reduce their ability to trap water (Zhao et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in the water absorption index of samples can be attributed to milling operation and thermal treatments given to coconut residue during preparation damaged the fibre chains and reduce their ability to trap water (Zhao et al, 2017). Specifically, mechanical treatments like dry milling can collapse the porous matrix formed by the carbohydrate chains that can trap water (Gao et al, 2020). Coconut residue was reportedly having a higher water absorption index than any other dietary fibre residues, including apple, potato and wheat bran fibres (Raghavendra et al, 2004) The swelling index of the aqueous suspension of starch is a reflection of the strength of the hydrogen bonding between the granules.…”
Section: Discussionmentioning
confidence: 99%